Changes in coal mining society in contemporary West Bengal, India - Sribas Goswami, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2011)
The Government of India has, in recent years, taken multiple steps to encourage private sector participation, adopt a more holistic approach towards expanding its coal base, and improve efficiency in the sector as a whole. However, the existing regulatory framework in India is not adequately developed or in tune with international standards that the extractive industries sector have been putting together. It is thus crucial for the Indian coal industry to consider changes in its regulatory environment to make it a par with the international standards to meet the critical requirement for energy security. In fact coal mining society is passing though havoc changes due to Government’s newly introduced multifold policies. The industrial relation now has changed immensely than the previous practices. Coal industry, which contributes 67 percent of total energy requirements of our country. After two phases nationalization the industry witnessed certain developments, which have implications for the human recourses management and industrial relation. In the beginning of the 90s one important event was the introduction of the new economic policy and this has a great influence over the coal mine sector. Impact of the policy Change is the introduction of a number of private operators in the coal production. Broadly, new economic policy initiated the gradual withdrawal of state from the control of basic industry and infrastructure. Coal mines are no exception in this regard.So the effect of new economic policy in the consequence of globalization also falls on the coal sectors. We now see what sort of impact of policy change has taken place upon the coal sector and coal workers. This article tires to examine the changes taken place due to policy changes and changes in general outlook of the people of coal mines in which they live. Now the industrial relation as well as the mechanism of work has been changed drastically. The traditional practice of work and mental outlook is gradually replacing with global method. It was noticed that people associated in this industry has started accepting the wider scope of work culture.